(untitled) (Periphērica, 2019)
Abstract: In Chapter IV: 22-23 of La consagración de la primavera by Alejo Carpentier, the main character Enrique is in New York. It is January 1943. The Second World War has begun. In contrast to what happens in the Spanish Civil War in the novel, which is told in the first person by the protagonist, the Second World War is told by the press. While reading journals and newspapers, Enrique observes a strange phenomenon that the novel defines as ‘euforia rusófila”. A lot of novels, films and articles in newspapers portrays the ideological enemy as a sort of a close friend to the USA, and the Russian people as hard worker, as well as honest and brave people. Is it an invention of an imaginative novelist or this description stems from a realistic portrays by the author? To verify it, we analyzed the books, articles and films that was produced during the short time in which Enrique was in New York. This article tries to check how, against the official narrative of the history, Carpentier grasps this forgotten historical episode and expresses it in one of his most important novels.